Tumor size is an independent negative prognostic factor for event free survival in children with differentiated thyroid cancer - Parvathareddy, Sandeep Kumar; Siraj, Abdul K.; Annaiyappanaidu, Padmanaban; Siraj, Nabil; Haqawi, Wael; Al-Sobhi, Saif S.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Endocrinology, 2022)
Background: The incidence of pediatric differentiated thyroid carcinoma (DTC) is increasing. Despite the advanced disease at presentation, the overall prognosis of DTC in children is excellent. The aim of this study is to investigate the risk stratifying factors for event free survival (EFS) of pediatric DTC from Middle Eastern ethnicity. Methods: Eighty-eight patients aged ≤18 years with diagnosis of primary DTC were retrospectively analyzed. Cox proportional hazards model were used to calculate Hazard Ratios (HR) and Kaplan–Meier analysis were conducted to investigate EFS. Results: Eighty-eight (23 males and 65 females) pediatric DTCs who underwent surgery and radioactive iodine therapy had been reported (median age at diagnosis 15 years; range 5.9-17.9), with lymph node metastasis (LNM) noted in 70.5% and distant metastasis in 13.6%. Mean follow-up was 8.4 years. Ten-year overall survival rate was 98.4% while 10-year EFS was 79.2%. EFS was negatively impacted by the presence of LNM, distant metastasis and tumor size >4cm. American Thyroid Association risk stratification did not impact EFS in our cohort. Multivariate analysis revealed tumor size >4cm (HR = 5.34; 95% confidence interval (CI) = 1.36 – 20.22; p = 0.0177) and distant metastasis (HR = 8.73; 95% CI = 1.48 – 60.05; p = 0.0154) as independent negative prognostic factors for EFS. Conclusions: Primary tumor size and the presence of distant metastasis at diagnosis are the only independent prognostic risk factors for EFS in pediatric DTC in Middle Eastern ethnicity. Children with tumor size over 4cm had poor EFS, which may justify the need of more aggressive treatment and frequent follow-up.